Alias Jesse James Alias Jesse James - Bowers, William, 1916-1987.; Beauchamp, D. D. (Daniel D.), 1908-1969.; McLeod, Norman Z., 1898-1964.; Hope, Bob, 1903-2003.; Fleming, Rhonda, 1922-; Corey, Wendell, 1914-1968.; St. Aubrey, Robert; Lawrence, Bert.; United Artists Corporation; Hope Enterprises, Inc.; MGM Home Entertainment Inc.; Twentieth Century Fox Home Entertainment, Inc. ([Los Angeles, CA] : MGM Home Entertainment ; Beverly Hills, Calif. : Distributed by 20th Century Fox Home Entertainment, 2007)
When Milford sells a large life insurance policy to 'T.J. James, ' a young man who says he's well-known, the broker thinks he has made a killing. But his elation is short- lived when he realizes that his new client is none other than Jesse James - who is already worth more dead than alive. Suddenly Milford finds himself saddled with a new commission: to go west, join the James gang and do everything possible to keep the deadliest outlaw in history alive.
Title from container.
Based upon a story by Robert St. Aubrey and Bert Lawrence.
Originally released as a motion picture in 1959.
Bob Hope, Rhonda Fleming, Wendell Corey.
Not rated.
DVD, region 1, full screen (1.33:1) and widescreen (1.66: 1) presentation; Dolby Digital mono., double-sided, NTSC.
Keywords: James, Jesse, -- 1847-1882 -- Drama; Insurance agents -- United States -- Drama; Insurance policies -- United States -- Drama; Criminal behavior -- United States -- Drama; Outlaws -- United States -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired; French language materials; Spanish language materials